ICT Diffusion in Developing Countries 2015
DOI: 10.1007/978-3-319-18254-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Technology Diffusion

Abstract: This chapter provides a theoretical framework of technology diffusion, which is defined as a dynamic and time-attributed process involving the transfer of information, knowledge and innovations, and standing for a continuous and gradual spread of new ideas throughout large-scale and heterogeneous societies. First, it extensively discusses theoretical technology diffusion concepts and models, explaining the technology diffusion trajectories by the use of S-shaped curves. Second, it presents the fundamental idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 234 publications
(266 reference statements)
0
2
0
Order By: Relevance
“…The extent of use of a new technology can be measured in a number of ways, three of which are most common: (i) absolute total usage/ownership at a given instant of time; (ii) usage/ownership relative to some total output measure, e. g. GDP; and (iii) total usage relative to some estimated post-diffusion (asymptotic or saturation) level of utilization [ 6 ]. Early and subsequent studies [ 7 – 12 ] found that the key temporal features of diffusion followed the typical pattern of a constrained S -shaped curve. Diffusion rates first increase and then decrease over time, featuring a phase of relatively rapid adoption sandwiched between an early interval of slow growth and a late segment of decelerated approach to saturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of use of a new technology can be measured in a number of ways, three of which are most common: (i) absolute total usage/ownership at a given instant of time; (ii) usage/ownership relative to some total output measure, e. g. GDP; and (iii) total usage relative to some estimated post-diffusion (asymptotic or saturation) level of utilization [ 6 ]. Early and subsequent studies [ 7 – 12 ] found that the key temporal features of diffusion followed the typical pattern of a constrained S -shaped curve. Diffusion rates first increase and then decrease over time, featuring a phase of relatively rapid adoption sandwiched between an early interval of slow growth and a late segment of decelerated approach to saturation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available regression models are basically extensions, generalizations or combinations of the growth laws originally proposed by Verhulst [ 13 ], Bass [ 14 ], and Gompertz [ 15 ]. Inasmuch as the present research is not directly concerned with the validation of diffusion models by the instruments of regression analysis, we refer the reader to comprehensive surveys [ 12 , 16 – 20 ] for more information in that direction.…”
Section: Introductionmentioning
confidence: 99%